Systematic Literature Review (SLR): Animation Video-Based Media in Science Learning at Elementary School - Assakhiy, Herfiana Putri; Izza, Naily Soimatul; Rohmah, Hajeng Laili; Fitriyani, Dila Eka; Fakhriyah, Fina; Ismaya, Erik Aditia (MultiTech Publisher, 2023)
Animated video is a combination of moving audio-visual media. Audio visual media rely on the senses of hearing and sight. This study aims to conduct a literature review related to the influence of video-animation-based media on science learning in elementary schools using the SLR (Systematic Literature Review) method. The data collection technique was carried out by finding sources of articles from national journals that have similar research sourced from the Google Scholar database with the help of the Publish or Perish application. The articles used were 5 articles that were obtained and met the specified inclusion and exclusion criteria. The articles collected were only published articles from 2018 to 2023. The results showed that the use of video-animation-based media can help students improve their abilities and understand the material contained in science subjects. Students become interested and very enthusiastic about animated video-based media, easily understand science material assisted by pictures that arouse students' interest in learning. In this animated video media can overcome boredom in students during the learning process takes place.